THE DYNAMIC OF CACI MULTIFUNCTION IN MANGGARAI ETHNIC NOWADAYS - Karolus Budiman Jama; I Wayan Ardika; I Ketut Ardhana; I Ketut Setiawan (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2020)
Manggaraian ethnic has a special art named Caci. The art holds and became an identity of the whole of Manggaraian. The art was begun as the ritual of farmer’s land fertility. In its developing, the aesthetic has gone under the multifunction in it show time. The art is not only performing for the shake of the local people culture, but also perform for the political interest as well as the catholic church in Mangggarai. This research used ethnographic method, data collected through the observation, interview, documentation, and triangulation. The research was done in Manggaraian ethnic of Flores. Every Caci performance has its own unique ideology. The ideology goes behind the cultural Caci performance is the ideology of fertility. The ideology goes behind the government interest of Caci performance is capitalism economy and political power. The church ideology is inclusivism through the inculturation languages. Keywords: dynamic, multifunction, caci, ideology, culture identity